Social networks, business strategy, and competitive advantage of private enterprises in China - Zhao, Shaoyu (2017)
This study focuses on how the social networks of entrepreneurs shape the business strategies adopted by the Chinese private enterprises and the role of social networks in sustaining competitive advantage. Using data collected from 418 surveys and 53 interviews with private entrepreneurs in Guangdong Province in 2013, this study investigates how entrepreneurs embedded in different business-to-business (B2B) networks and business-to-government (B2G) networks perceive the role of social networks in the design and implementation of business strategies. This study also explores the types of political participation private entrepreneurs use to overcome discrimination that undermines their legitimacy and constrains access to resources. The findings from logistic regression and analysis of interviews indicate that private entrepreneurs perceive that B2B networks enable their firms to access accurate information to seize business opportunities, and strengthen long-term oriented buyer-supplier relationships. B2G networks help private firms to overcome the administrative obstacles and access state controlled resources. Private entrepreneurs also employ various political strategies to advance their interests. They usually value more highly membership of the People’s Congress (PC) or People’s Political Consultative Conference (PPCC) over membership of the Communist Party in strengthening B2G connections and establishing firm legitimacy. Overall, this study of Guangdong entrepreneurs contributes to the business literature in seeking to integrate theories about social networks and business strategy. It provides empirical data on how the private enterprises in China use their social networks in business. The results extend the understanding of social network in business strategy and contribute to the studies on social network theory and strategic management in transition countries. A deeper understanding of the role of the social networks in the business environment in China helps managers to choose a more suitable strategy to compete in the market.